Prevalence of Esophageal Eosinophilia, Eosinophilic Esophagitis, and Lymphocytic Gastritis in Children with Celiac Disease: A Saudi Tertiary Center Experience - Meshari A. Alaifan; Ammar Khayat; Rana Y. Bokhary; Abdulhameed Ibrahim; Yagoub Bin-Taleb; Bakr H. Alhussaini; Omar I. Saadah (Canadian Journal of Gastroenterology and Hepatology)
Background. Celiac disease (CD) is an immune-mediated enteropathy that has been associated with other immune-related gastrointestinal disorders, such as eosinophilic esophagitis (EoE) and lymphocytic gastritis (LG). To our knowledge, this is the first study in Saudi Arabia that has described such an association. Aim. To evaluate the prevalence of EoE and LG in children and adolescents with CD. Methods. This was a retrospective cross-sectional study of all pediatric patients (aged 0–18 years) with CD following up at King Abdulaziz University Hospital, between January, 2014, and December, 2021. The study examined clinical, demographic, endoscopic, and histopathological data. Results. Seventy-five patients with CD were included in the analysis. The median age was 12 years (range, 2–18 years). Male constituted 54.7% of the overall cohort (n = 41). The most common clinical symptoms were short stature (54.7%), weight loss (34.7%), abdominal pain (33.3%), abdominal distension (29.3%), anorexia (29.3%), diarrhea (24%), and vomiting (21.3%). The esophageal biopsy results reported were basal cell hyperplasia in 24 patients (32.9%), esophageal eosinophilia in 23 patients (31.5%), and EoE in 3 patients (4.1%). The gastric biopsy results were normal in 40 patients (53.3%). The most common abnormality was chronic inactive gastritis with no Helicobacter pylori (HP) infection (16%). LG was found in 3 patients (4%). Conclusions. The prevalence of EoE in this cohort of patients with CD was lower than the prevalence recorded in a number of other studies. Further studies are needed to determine the effects of a gluten-free diet (GFD) on EOE and LG.